Analysis Of Feasibility And Enhancing Competitiveness Farming Seaweed In Situbondo District - Sulistyaningsih, Sulistyaningsih; Muhlis, Abdullah (CV. Inara, 2024)
This study aims to determine the feasibility of seaweed farming, identify the factors that affect the feasibility of seaweed farming, and determine the development strategy of seaweed farming. This Research took place in Situbondo used Slovin data sampling formula. The data were analysed by using RCR and SWOT. The results show that the first period of grass farming is not feasible because family labor is calculated and the second period is feasible because the variable cost of purchasing bamboo and family labor were not calculated. Seaweed farming is prospective with strategies developeded through improved markets and partnerships as well as institutions.